1997
DOI: 10.1071/aj96057
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Ocean Concentrations of Aromatic Hydrocarbons From Produced Formation Water Discharges to Bass Strait, Australia

Abstract: Previous assessment of dispersion modelling, toxicity testing, and characterisation of produced formation water (PFW) discharges into Bass Strait indicated a very low environmental risk from PFW to the marine environment. Peak PFW concentrations can exceed the effect levels (ECs0 or LC50) measured in 24-96 hr laboratory toxicity tests only within distances of tens of metres from the discharge point. In this assessment, the field monitoring of aromatic hydrocarbons in the water column (which are in low concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The sampling device provided timeintegrated samples over approximately one week, and the results showed that the ratio between concentration of PAH at the sampling point to that in the discharge was 1:20,000 (25).…”
Section: Field Studiesmentioning
confidence: 99%
“…The sampling device provided timeintegrated samples over approximately one week, and the results showed that the ratio between concentration of PAH at the sampling point to that in the discharge was 1:20,000 (25).…”
Section: Field Studiesmentioning
confidence: 99%
“…The social and economic significance of effect can be considered in terms of impact on conservation values, recreational or commercial fishing, tourism, and the benefit to the community of the petroleum activity. If spatial scale of the effect was limited to the immediate area around an offshore facility and the significance of the effect was considered to be low, then the risk is likely to be acceptable (Terrens and Tait, 1996). Conversely, if the spatial scale of the effect was widespread and the survival or reproductive capacity of marine organisms significantly reduced, then the risk is likely to be considered unacceptable survival of those populations would be at risk.…”
Section: Assessing Environmental Effects and Risks And Determining Acmentioning
confidence: 99%